Kinetics of Phase Decomposition in MAX Phases - A Comparative Diffraction Study - Low, It-Meng (Jim); Pang, W. (Australasian Ceramic Society, 2011)
The susceptibility of MAX phases to thermal dissociation at 1300-1550 °C in high vacuum has been studied using in-situ neutron diffraction. Above 1400 °C, MAX phases decomposed to binary carbide (e.g. TiCx) or binary nitride (e.g. TiNx), primarily through the sublimation of A-elements such as Al or Si, which results in a porous surface layer of MXx being formed. Positive activation energies were determined for the decomposition of MAX phases except for Ti3AlC2 where negative activation energy of 71.9 kJ mol-1 was obtained due to formation of fine pores on TiCx. The kinetics of isothermal phase decomposition at 1550 °C was modelled using a modified Avrami equation. An Avrami exponent (n) of < 1.0 was determined, indicative of the highly restricted diffusion of Al or Si between the channels of M6X octahedra. The characteristics of thermal stability and phase transition are discussed.